The Correlation Between Lifestyle And Menopausal Symptoms Among Women In Three Big Cities Of Indonesia - Shaffa Annisa, -
Abstract Background: Menopause is a natural physiological event that occurs in middle-aged women and is characterized by the cessation of menstruation for at least one year following the last menstrual period. Menopause symptoms include somatic symptoms, psychological symptoms, and urogenital symptoms. Menopause symptoms and their severity vary from person to person due to numerous factors, one of which is a persons lifestyle. Lifestyle aspects related to menopausal symptoms and observed in this study include dietary habits, physical activity, stress levels, and sleep habits. This research examined at the correlation between lifestyle and symptoms in postmenopausal women. Methods: This cross-sectional study was conducted using a random sampling technique in which 70 postmenopausal women who met the inclusion and exclusion criteria were selected from 3 communities in Batam, Makassar and Surabaya. The variables observed included menopausal symptoms as measured by the Menopause Rating Scale (MRS) instrument and lifestyle as measured by the Simple Lifestyle Indicator Questionnaire (SLIQ) and Pittsburgh Sleep Quality Index (PSQI) instruments. Results: There was a strong correlation between lifestyle and menopausal symptoms (p=0.007), with a unidirectional and adequate relationship between the two variables (r=0.318). However, there is no significant relationship between sleep quality and menopausal symptoms (p=0.150), with a unidirectional and very weak relationship between the two variables. Conclusion: Postmenopausal women may experience fewer symptoms the healthier their lifestyle choices, but there is no solid evidence linking poor sleep to menopausal symptoms.